2015
DOI: 10.1038/srep15792
|View full text |Cite
|
Sign up to set email alerts
|

Multiblock copolymers exhibiting spatio-temporal structure with autonomous viscosity oscillation

Abstract: Here we report an ABA triblock copolymer that can express microscopic autonomous formation and break-up of aggregates under constant condition to generate macroscopic viscoelastic self-oscillation of the solution. The ABA triblock copolymer is designed to have hydrophilic B segment and self-oscillating A segment at the both sides by RAFT copolymerization. In the A segment, a metal catalyst of chemical oscillatory reaction, i.e., the Belousov-Zhabotinsky (BZ) reaction, is introduced as a chemomechanical transdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 45 publications
3
20
1
Order By: Relevance
“…Interestingly, in the case of these ABC triblock copolymers, sequential aggregation was observed in the reduced state, that is, the oscillating profile showed sharp top peaks. In contrast, in a previous study using the ABA triblock copolymer, a plateau region appeared in the oscillating profiles in the reduced state9. Therefore, we conclude that due to the stepwise aggregation process, the micelle structures of the ABC triblock copolymer synthesized in this study must have fewer loop chains than those of the ABA triblock copolymer.…”
Section: Resultscontrasting
confidence: 96%
See 3 more Smart Citations
“…Interestingly, in the case of these ABC triblock copolymers, sequential aggregation was observed in the reduced state, that is, the oscillating profile showed sharp top peaks. In contrast, in a previous study using the ABA triblock copolymer, a plateau region appeared in the oscillating profiles in the reduced state9. Therefore, we conclude that due to the stepwise aggregation process, the micelle structures of the ABC triblock copolymer synthesized in this study must have fewer loop chains than those of the ABA triblock copolymer.…”
Section: Resultscontrasting
confidence: 96%
“…Remarkably, as seen in Fig. 3b, when the polymer concentration was 5.0 wt%, the viscosity amplitude reached a maximum of 1,960 mPa s. This value is comparable to the amplitude occurring in living amoeba, and about 10 3 times larger than those observed in previous reports789. Supplementary Fig.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…[7,8] To realize autonomous oscillatory behaviors that exist in living systems by using synthetic materials,w eh ave developed "self-oscillating" gels which exhibit autonomous periodic swelling/deswelling changes driven by an oscillatory chemical reaction. [13][14][15][16][17] In addition to our studies,o ther groups have also reported self-oscillating polymer materials. [13][14][15][16][17] In addition to our studies,o ther groups have also reported self-oscillating polymer materials.…”
mentioning
confidence: 99%